Design of carbon nanotube field effect transistor (CNTFET) small signal model - Soheli Farhana (Institute of Advanced Engineering and Science, 2020)
The progress of Carbon Nanotube Field Effect Transistor (CNTFET) devices has facilitated the trimness of mobile phones, computers and all other electronic devices. CNTFET devices contribute to model these electronics instruments that require designing the devices. This research consists of the design and verification of the CNTFET device's small signal model. Scattering parameters (S-parameters) is extracted from the CNTFET model to construct equivalent small model circuit. Current sources, capacitors and resistors are involved to evaluate this equivalent circuit. S-parameters and small signal models are elaborated to analyze using a technique to form the small signal equivalent circuit model. In this design modeling process, at first intrinsic device's Y-parameters are determined. After that series of impedances are calculated. At last, Y-parameters model are transformed to add parasitic capacitances. The analysis result shows the acquiring high frequency performances are obtained from this equivalent circuit.